The Government's Accountability in Granting Permits for Keeping Protected Wildlife as Pets - Safitri, Sifa' Ulya; Rosnawati, Emy (Universitas Muhammadiyah Sidoarjo, 2023)
This study investigates governmental accountability regarding permits granted for the domestication of protected wildlife. Employing a juridical-normative method with a conceptual approach, it scrutinizes scenarios where wild animals, under domestic care, cause harm. Findings indicate that accountability remains with the owner in the event of wildlife attacks. However, negligence in adhering to granted permits resulting in animal death invokes penalties per Conservation Law No. 5/1990: imprisonment up to 5 years and fines up to Rp. 100,000,000. Notably, dispensations granted due to permit discrepancies underscore the complexity of the issue. This research underscores the legal intricacies and implications of wildlife ownership, stressing the imperative of stringent compliance with conservation laws to preserve endangered species. Highlights: Wildlife Ownership Responsibility: Owners bear accountability for wild animal actions under domestic care. Permit Compliance and Implications: Negligence in permit adherence may lead to legal penalties and wildlife protection law violations. Conservation Law Enforcement: Strict compliance is crucial to safeguard endangered species and maintain biodiversity. Keywords: Wildlife ownership, Legal accountability, Conservation law, Permit compliance, Endangered species